Plumbing System Planning (Clean Water and Wastewater Installation) at the Pontianak State Polytechnic Student Dormitory - Ayuni, Tania Diah; Fikriyah, Nabila Adli; Ryanti, Eva; Haffiyan, Qalbi; Widhiastuti, Rahayu; Rizal (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
The Politeknik Negeri Pontianak Student Dormitory consists of four floors with a capacity of 345 people, which is dependent on water supply from the Regional Water Company (PDAM). Water availability is often disrupted, especially in the morning. Therefore, this study aims to design a plumbing system that integrates rainwater harvesting (RWH) as an alternative water source, along with clean water and wastewater systems that comply with national standards. The methodology used includes water demand analysis based on the number of residents, evaluation of rainwater harvesting potential from the roof, reservoir capacity calculations, pump specifications, and piping networks up to the septic tank based on Indonesian National Standards (SNI) and other standards. Additionally, the designed piping system considers distribution efficiency, adequate water pressure, and safe sanitation. Based on the calculation in this planning, the use of a rainwater harvesting system can minimize PDAM usage by 11.18%. This plan is expected to provide a sustainable solution for clean water supply in the campus environment, particularly at the Pontianak State Polytechnic Student Dormitory.